2014
DOI: 10.1016/j.applthermaleng.2013.11.056
|View full text |Cite
|
Sign up to set email alerts
|

High resolution microtomography-based CFD simulation of flow and heat transfer in aluminum metal foams

Abstract: Engineering disseminates novel research related to the design, development and demonstration of components, devices, equipment, technologies and systems involving thermal processes for the production, storage, utilization and conservation of energy, with a focus on engineering application. The journal publishes high-quality and high-impact Original Research Articles, Review Articles, Short Communications and Letters to the Editor on cutting-edge innovations in research, and recent advances or issues of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(45 citation statements)
references
References 44 publications
1
38
0
Order By: Relevance
“…Similarly, the permeability values show a weak decrease with increasing surface area of the foams, with some samples presenting a small deviation from this general trend. This same trend was observed in pore-scale simulation results by Ranut et al (2014). Figure 10a depicts the CFD permeability values for all foams as a function of the specific surface area.…”
Section: Comparison To Experimentssupporting
confidence: 64%
See 2 more Smart Citations
“…Similarly, the permeability values show a weak decrease with increasing surface area of the foams, with some samples presenting a small deviation from this general trend. This same trend was observed in pore-scale simulation results by Ranut et al (2014). Figure 10a depicts the CFD permeability values for all foams as a function of the specific surface area.…”
Section: Comparison To Experimentssupporting
confidence: 64%
“…As shown in the work of Ranut et al (2014), open-cell metal foams normally have the pores and struts elongated along one particular direction due to their manufacturing process. Simulations results obtained by Ranut et al (2014) have shown that changing the direction of the incoming flow can cause deviations of up to 20 % on the pressure gradient. Unfortunately, anisotropy in the foam structure and its effect on the flow were not evaluated in the present work, but could explain some of the discrepancies found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross sectional shape of metal fibre (strut) changes with porosity, from a circle at a porosity of 85% to a concave triangle when the porosity reaches 97% [15,21,39]. To include the effect of the thickness ratio of the nodes and struts, the predicted ETC from the Coquard et al model [18] was compared with experimental results with cubic and parallelepipedic node shapes.…”
Section: Validity With Correlations and Modelsmentioning
confidence: 99%
“…X-ray microcomputed tomography ( -CT) enables to capture and reconstruct the complex structure of porous media in accurate details [34][35][36][37]. Thus, simulations with realistic representations of metal opencell foams were carried out using finite element method for the analysis of heat transfer properties of metal foams [34,[37][38][39].…”
Section: G Modelmentioning
confidence: 99%